2012
DOI: 10.2165/11630550-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Cooling and Sports Performance

Abstract: Pre-cooling is used by many athletes for the purpose of reducing body temperature prior to exercise and, consequently, decreasing heat stress and improving performance. Although there are a considerable number of studies showing beneficial effects of pre-cooling, definite conclusions on the effectiveness of pre-cooling on performance cannot yet be drawn. Moreover, detailed analyses of the specific conditions under which pre-cooling may be most promising are, so far, missing. Therefore, we conducted a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 62 publications
9
98
1
3
Order By: Relevance
“…Essa relação entre a FC e o consumo de oxigênio demonstra que o comportamento da FC durante o exercício depende, em grande parte, da demanda metabólica na musculatura ativa, expressando um aumento da FC, com o aumento da intensidade do exercício. O pré-resfriamento, porém, induziria à diminuição do estresse cardíaco, bem como à redução do gasto metabólico geral e supressão dos sinais centrais de inibição 28 .…”
Section: Discussionunclassified
“…Essa relação entre a FC e o consumo de oxigênio demonstra que o comportamento da FC durante o exercício depende, em grande parte, da demanda metabólica na musculatura ativa, expressando um aumento da FC, com o aumento da intensidade do exercício. O pré-resfriamento, porém, induziria à diminuição do estresse cardíaco, bem como à redução do gasto metabólico geral e supressão dos sinais centrais de inibição 28 .…”
Section: Discussionunclassified
“…A lower core body temperature at a given point during exercise enables humans to perform physical activity for a longer duration during constant pace exercise or at higher intensities during self-paced exercise (Jones et al, 2012a(Jones et al, , 2012b. A beneficial effect on performance arises from a reduced sweat rate and a lower plasma volume reduction, which would decrease the risk of dehydration (Ross, et al, 2013;Wegmann et al, 2012). In addition to the physiological effects of MCSs, psychological responses are non-negligible.…”
Section: Effectiveness Of Mcssmentioning
confidence: 99%
“…Likewise, Wegmann et al 37 found a 6.6% improvement in performance when cooling was used during exercise in the heat, with the largest improvements occurring during endurance events. While cold drinks and cool packs have shown the largest improvements in performance when examining the influence of the modality itself, 37 it is suggested that using multiple forms of cooling may provide a greater benefit for performance. 24 The timing of body cooling has also been well investigated, particularly with cooling before exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has supported the use of ice bags to improve performance, with reported performance improvements on the magnitude of 5.6%. 37 Although this modality is often used due to its accessibility and easy implementation, the extent to which it can cool the body over other modalities is rather low, with a cooling rate on the order of 0.03°C/min. 38…”
Section: Ice Bagsmentioning
confidence: 99%